مفهوم الرسول والنبي - حسن الخطاف (International Institute of Islamic Thought, 2018)
يمثل مفهوما الرسالة والنبوة صلة الله تعالى بخلقه، وهما منحة منه عزَّ وجلَّ؛ إذ ذكرهما وذكر ما يتَّصل بهما أكثر من مئتي مرة بأساليب عدَّة. وقد أسهمت هذه الكثرة في إشعال جذوة الخلاف بين المتكلمين، ومَن سار على إثرهم من المفسرين الذين حاولوا تحديد المراد بهذين المفهومين: هل يؤديان معنىً واحداً بحسب جمهور المعتزلة؟ هل يوجد اختلاف بينهما مثلما يقول جمهور أهل السُّنة؟ تَبيَّن لنا أنَّ الدراسة المسْحية للنصوص القرآنية لم تُؤخذ في هذه التوجُّهات بالاعتبار، فجاء هذا البحث ليسدّ هذه الثغرة انطلاقاً من دلالات النص القرآني وسياقاته بعد الكشف عن نظر المتكلمين ومَن سار معهم في هذه المسألة، وخلُص إلى عدم وجود اختلاف بين مفهومي الرسول والنبي. Prophethood and Messengership are considered a link between God and His creation. The two terms and what is related to them have been mentioned in the Gracious Qur'an more than two hundred times in several ways. This fact has sparked a controversy among theologians and later among exegetes to explain what is meant by both terms; are messenger and prophet synonyms as argued by the majority of the Mu'tazilites? Or is there a difference between them as argued by the majority of Ahlu Al-Sunnah? No exhaustive survey of the Quranic text has been conducted for this purpose. This study comes to fill this gap, based on the Qur'anic text and context. The conclusion was that there is no difference between the concept of the Prophet and the concept of the Messenger.